Estimation of the Postmortem Duration of Mouse Tissue by Electron Spin Resonance Spectroscopy. (25th May 2011) - Ito, Shinobu; Mori, Tomohisa; Kanazawa, Hideko; Sawaguchi, Toshiko
Abstract : Electron spin resonance (ESR) method is a simple method for detecting various free radicals simultaneously and directly. However, ESR spin trap method is unsuited to analyze weak ESR signals in organs because of water-induced dielectric loss (WIDL). To minimize WIDL occurring in biotissues and to improve detection sensitivity to free radicals in tissues, ESR cuvette was modified and used with 5, 5-dimethtyl-1-pyrroline N-oxide (DMPO). The tissue samples were mouse brain, hart, lung, liver, kidney, pancreas, muscle, skin, and whole blood, where various ESR spin adduct signals including DMPO-ascorbyl radical (AsA ∗ ), DMPO-superoxide anion radical (OOH), and DMPO-hydrogen radical (H) signal were detected. Postmortem changes in DMPO-AsA ∗ and DMPO-OOH were observed in various tissues of mouse. The signal peak of spin adduct was monitored until the 205th day postmortem. DMPO-AsA ∗ in liver (y = 113.8 – 40.7 log (day), R 1 = - 0.779, R 2 = 0.6, P < .001 ) was found to linearly decrease with the logarithm of postmortem duration days. Therefore, DMPO-AsA ∗ signal may be suitable for detecting an oxidation stress tracer from tissue in comparison with other spin adduct signal on ESR spin trap method.